2016
DOI: 10.1371/journal.pone.0165884
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Based Metabolomics Comparison of Liver Grafts from Donors after Circulatory Death (DCD) and Donors after Brain Death (DBD) Used in Human Orthotopic Liver Transplantation

Abstract: Use of marginal liver grafts, especially those from donors after circulatory death (DCD), has been considered as a solution to organ shortage. Inferior outcomes have been attributed to donor warm ischaemic damage in these DCD organs. Here we sought to profile the metabolic mechanisms underpinning donor warm ischaemia. Non-targeted Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry metabolomics was applied to biopsies of liver grafts from donors after brain death (DBD; n = 27) and DCD (n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…One major finding of this study is the greater metabolism of tryptophan (TRP) via the kynurenine pathway (KP) in the NMP group with subsequently increased tissue concentrations of kynurenine (KYN) and kynurenate (KYNA). The difference in tryptophan metabolism during NMP compared to SNMP represents a clinically significant finding, as two studies found higher levels of KYN in transplanted livers that experienced primary nonfunction compared to livers with normal function [ 17 , 20 ]. Though KYNA levels were not reported, this highlights the therapeutic potential of this metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One major finding of this study is the greater metabolism of tryptophan (TRP) via the kynurenine pathway (KP) in the NMP group with subsequently increased tissue concentrations of kynurenine (KYN) and kynurenate (KYNA). The difference in tryptophan metabolism during NMP compared to SNMP represents a clinically significant finding, as two studies found higher levels of KYN in transplanted livers that experienced primary nonfunction compared to livers with normal function [ 17 , 20 ]. Though KYNA levels were not reported, this highlights the therapeutic potential of this metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While the higher energy charge ratios are attributed to the lower metabolic activity at subnormothermic temperatures, the depletion of glutathione is likely due to the inability to expend ATP needed to resynthesize glutathione after its breakdown. Similarly, several clinical studies have demonstrated a correlation between higher concentrations of glutathione metabolites and early allograft dysfunction [ 17 , 18 ]. Therefore, supplementation of the circulating perfusate during SNMP with exogenous glutathione could be another potential therapy to improve a DCD graft’s ability to tolerate oxidative stress during transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review on the use of metabolomics to discover liver biomarkers for transplantation outcomes in liver tissue biopsies highlighted promising results [17]. These first studies identified lipid molecules [18][19][20], tryptophan, kynurenine and S-adenosylmethionine as liver biomarkers [21,22].…”
Section: Of 13mentioning
confidence: 99%